Men’s Decision to Use Contraception in Surabaya, Indonesia: Perceived Barriers, Seriousness and Benefits - Nastiti, Aria Aulia; Pradanie, Retnayu; Cahyono, Budi (International Journal of Psychosocial Rehabilitation, 2020)
The high rate of population growth, and the frequency at which mothers give birth is still a problem in Indonesia. Contraceptive use is still dominated by women. However, male decisions to use contraception are still low in many countries. This study aimed to identify the correlation of the perceived barriers, perception of seriousness and perception of benefits with men’s decision to use contraception in Surabaya, Indonesia. A cross- sectional study was carried out with 162 men who were married in Surabaya. Data were collected using questionnaires. Spearman’s rho values were used to determine the correlations of perceived benefits, perceived seriousness, perceived barriers and men’s decision to use contraception. This study found that perceived barriers (r=0.487, P = 0.001), perceived seriousness (r= 0.779, P=0.001) and benefits (r = 0.779, P = 0.001) were noted to be correlated with the men’s decision to use contraception in Surabaya, Indonesia. It can be concluded that perception of barriers, perception of seriousness and benefits are related to men’s decision to use contraception; thus, developing good perceptions and benefits should be properly promoted.